ABERRANT INTRANUCLEOLAR MATURATION OF RIBOSOMAL PRECURSORS IN THE ABSENCE OF PROTEIN SYNTHESIS - Craig, Nessly C. (The Rockefeller University Press, 1970)
To help elucidate the role of protein in the maturation of ribosomal RNA in cultured L cells, we have studied the effects of cycloheximide upon the maturation process and upon the intranucleolar ribonucleoprotein particles containing the "preribosomal RNA's." Five parameters of these particles were analyzed: (a) extractability, (b) sedimentation characteristics in sucrose gradients, (c) RNA composition, (d) buoyant density in CsCl gradients, and (e) effects of increased ionic strength on the buoyant density. When protein synthesis is inhibited, the rate of conversion of the precursor 45S ribosomal RNA is rapidly diminished, falling to less than 30% of the control rate within 1 hr. Nevertheless, in terms of the first three parameters there is no difference between control and cycloheximide nucleolar particles. However, the cycloheximide particles have a lower and more heterogeneous buoyant density and a more variable response to increased ionic strength. The results imply that the protein composition of the cycloheximide particles is different from that of particles from control cells, and that the entire protein complement is not necessary for the first cleavages in the maturation process, although it is necessary for the normal rate of processing and for the eventual appearance of both 18S and 28S rRNA in mature ribosomes.